HUBUNGAN PENGETAHUAN DAN SIKAP TERHADAP TINDAKAN IBU HAMIL TENTANG DETEKSI DINI TANDA-TANDA BAHAYA KEHAMILAN DI PUSKESMAS MEDAN DELI TAHUN 2015 - sarah ardillah; Sri Rahayu Sanusi; Maya Fitria (Gizi, Kesehatan Reproduksi dan Epidemiologi, 2015)
ABSTRACT Maternal Mortality Rate (MMR) is one indicator of the health status of the community. In the developing nations, maternal morbidity and mortality to be a problem for a long time. Maternal deaths mainly occur during pregnancy and childbirth. Based on the background of the problem and the results of preliminary studies in the public health centers of Medan Deli K1 coverage data obtained in August 2014 at 62.5%, whereas only 60.3% K4 coverage. The achievement of Minimum Service Standards (MSS) that the health field K1 and K4 coverage in pregnant women was 95% in 2015 but this targets are yet to be achieved. This is due to very low interest of pregnant women to carry out medical examinations to health workers in the context of early detectionof pregnancy danger signs. This research aims to understand the relationship between knowledge and attitudes towards the actions of pregnant women about early detection of danger signs of pregnancy in the PublicHealthCenters of Medan Deli 2015. Type of research was descriptive analytical with cross-sectional design. To see the correlation between knowledge and attitudes of pregnant women with early detection measures the danger signs of pregnancy in the Public HealthCenters of Medan Deli 2015. The sample in this researchwas had the third trimester pregnant women at high risk of pregnancy and childbirth. The results of chi-square test showed that the independent variables (knowledge and attitude) significantly (associated) with detection measures the danger signs of pregnancy (p = 0.001).Based on the results of research and discussion was conclude that there is a relationship between knowledge and attitudes of pregnant women with actions danger signs of pregnancy.Suggestions are that pregnant women to antenatal health care on a regular basis to allow the detection of risk factors that affect the health of the mother and baby.